What is functionalism? - Villena Saldaña, David (2017)
This paper explains the main theses of functionalism about mental states. This view is taken as a response addressed to the metaphysical aspect of the mind-body problem. Thus it is said what distinguishes functional properties as second-order properties, and how to understand supervenience and multiple realizability. The paper applies these ideas to machine functionalism and analytic functionalism, the two main versions of functionalism.